Platelet‐Derived Growth Factor B Is a Key Element in the Pathological Bone Formation of Ankylosing Spondylitis. (9th December 2022) - Jo, Sungsin; Lee, Seung Hoon; Park, Jinsung; Nam, Bora; Kim, Hyunsung; Youn, Jeehee; Lee, Seunghun; Kim, Tae‐Jong; Sung, Il‐Hoon; Choi, Sung Hoon; Park, Ye‐Soo; Inman, Robert D; et al.
ABSTRACT: Enthesophyte formation plays a crucial role in the development of spinal ankylosis in ankylosing spondylitis (AS). We aimed to investigate the role of platelet‐derived growth factor B (PDGFB) in enthesophyte formation of AS using in vitro and in vivo models and to determine the association between PDGFB and spinal progression in AS. Serum PDGFB levels were measured in AS patients and healthy controls (HC). Human entheseal tissues attached to facet joints or spinous processes were harvested at the time of surgery and investigated for bone‐forming activity. The impact of a pharmacological agonist and antagonist of platelet‐derived growth factor B receptor (PDGFRB) were investigated respectively in curdlan‐treated SKG mice. PDGFB levels were elevated in AS sera and correlated with radiographic progression of AS in the spine. Mature osteoclasts secreting PDGFB proteins were increased in the AS group compared with HC and were observed in bony ankylosis tissues of AS. Expression of PDGFRB was significantly elevated in the spinous enthesis and facet joints of AS compared with controls. Moreover, recombinant PDGFB treatment accelerated bone mineralization of enthesis cells, which was pronounced in AS, whereas PDGFRB inhibition efficiently reduced the PDGFB‐induced bone mineralization. Also, PDGFRB inhibition attenuated the severity of arthritis and enthesophyte formation at the joints of curdlan‐treated SKG mice. This study suggests that regulating PDGFB/PDGFRB signaling could be a novel therapeutic strategy to block key pathophysiological processes of AS. © 2022 American Society for Bone and Mineral Research (ASBMR).